(untitled) (PJDOL, 2023)
Virtual Learning is an emerging model in a distance mode of education. Due to advancement in technology, the concept of virtual learning has also prevailed in the job industry specially in the form of electronic internship or simply e-internship. It is not only providing opportunities for employers and employees but there are many challenges that are arising due to technology competency of interns in a remote learning environment.